INDUSTRIAL STRUCTURE AND TRANSMISSION OF MONETARY POLICY IN LATIN AMERICAN COUNTRIES - Quintero Otero, Jorge David (Investigación Económica, 2018)
Based on data from the manufacturing industry and its subsectors, this article shows the impact of monetary policy according to the industrial structure in Brazil, Chile, Colombia, Mexico and Peru, the five Latin American countries adopting the system of inflation targeting for the longest time. Results show that the impact of monetary policy on industrial production is stronger in countries where the interest rate channel is more relevant, since the subsectors producing capital goods and durable consumer goods are more sensitive to monetary decisions. These results are closely linked to the role of price rigidities on the differential impact of monetary policy on industrial subsectors.